Improving Beginning Reading Ability Using Learning Media Letters on Class 1 Students - Lasmini, Panti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This article discusses the use of letter card learning media to improve the ability to read the beginning in students of grade 1 SDN 1 Dawungan lesson year 2020/2021. One of the factors that cause students' reading ability to be low is the process of learning activities that still use conventional media by using whiteboards and teacher-centered learning processes so that learners become less active. Learning activities that use the medium of letter card learning make learners will be interested and feel fun so as to improve the ability to read the beginning of students in grade 1 SDN 1 Dawungan.